The Impact of Generational Gaps on Turnover Intentions in Islamic HRM Settings - Bawasa, Salmi; Othman, Abdul Kadir (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2024)
The study aims to determine whether Islamic HRM can influence employee turnover intention with the moderating effect of generational gaps. Employee turnover intention impacts organizations, such as decreased productivity, low staff morale, and increased re-hiring costs. Finding the reasons for employee turnover intention is essential based on the given factors. This study adopts a positivist research design with a correlational study approach. A total of 277 respondents from multinational corporations (MNCs) participated in the study. The study adopts questionnaires as the research instrument. Findings revealed that Islamic HRM practices, that is, Islamic recruitment, selection, retrenchment management, and Islamic performance management and compensation management, highly influence employee turnover intention. Generation Z/iGens also highly moderated Islamic performance management, compensation management, and employee turnover intention.